Prediktor Komplikasi Dengue Shock Syndrome (DSS) pada Pasien Pediatri dengan Dengue Hemorrhagic Fever (DHF) - Ahmad Arkan Ichsan; Khairun Nisa Berawi; Neema Putri Prameswari; Ratu Nirmala Wahyunindita (Medula, 2020)
Dengue Hemorrhagic Fever (DHF) are tropical infectious diseases prevalent in tropical, subtropical and temperate climate countries, complications of DHF that leads to Dengue Shock Syndrome (DSS) may have drastic implications towards the mortality of pediatric patients. Ongoing assessment is still proceeding on Risk factors for the patient’s progression to DSS and there are several predictors utilized on patient follow-up that may indicate high risk of clinical symptom progression to DSS. Several predictors are identified to be the female gender, age between 6-10 years, hepatomegaly, late clinical management, heavy plasma leakage, obesity, spontaneous bleeding, gastrointestinal bleeding and presentations of ascites and pleural effusion. Several lab examinations include leucopenia, prolonged aPTT, low platelet count, thrombocytopenia, hematocrit of ≥ 40, low lipid profile, hypoalbuminemia, hypoproteinemia. There are also other predictors identified such as high Troponin T levels, NS1Ag expression, NK and NKT gene expression, elevated Vitamin D levels, Fatty acid levels. high sTM levels, elevated Chymase enzyme serum levels and elevated lactate serum levels. The usage of machine learning and algorithms may also prove useful in predicting DSS complications through pattern identification. There is a wide array of current and new methodologies to predict DHF progression to DSS, and further review analysis may be needed to determine concrete indicators for predicting DHF progression to DSS. Newer methods may prove useful, and would need further testing to ensure its capabilities on predicting DSS.